ChemInform Abstract: Pd‐Catalyzed Dehydrogenative Annulation Approach for the Efficient Synthesis of Phenanthridinones. Issue 48 (10th November 2016) - Li, Xinyao; Pan, Jun; Song, Song; Jiao, Ning
Abstract: The title process allows the synthesis of a wide range of phenanthridinones from aryl iodides and aryl carbamic chlorides.